A MENCIPTAKAN IKLIM BELAJAR KONDUSIF: STUDI MANAJEMEN KELAS DI SMPIT SYIFA FIKRIYA CIKANDE: Manajemen Kelas - Yuniar, Euis Ismayati; Imron, Taufik; Kangiden, Farida Ariyani; Turrohmah, Saila; Trikawati, Trikawati (JEDLISH : Journal Of Education and English Language Teaching, 2025)
This research aims to apply classroom management and analyze its impact on student learning engagement using Mixed Methods. Creating a conducive learning climate is a challenge at SMPIT Syifa Fikriya Cikande due to the diverse student personalities and classroom dynamics. A qualitative approach was used to describe teacher implementation through observation, interviews, and documentation, while a quantitative approach measured the relationship between classroom management, learning climate, and student engagement through questionnaires with 34 purposive sample students. The research results show teachers effectively organizing the classroom, dividing educational time into structured stages, implementing classroom rules, and building positive interactions through praise, tutorials, and group dialogue. This results in a conducive learning climate, characterized by an orderly classroom, focused students, and harmonious cooperation. A conducive learning climate increases student engagement, evident in the courage to ask questions, respond to problems, actively participate in dialogue, and complete assignments enthusiastically. This research emphasizes the application of real, adaptive, and evidence-based classroom management that can create a conducive learning climate and directly improve the quality of education.